The positive impact of bicultural identity on emotional, cognitive, and behavioral engagement: An exploratory analysis - Rabi, Fazli; Fengqi, Ma; Aziz, Muhammad (American Journal of Creative Education, 2023)
This study investigates the impact of dual cultural backgrounds on student engagement in school, specifically focusing on minority students in China who are adapting to a new culture. It examines the emotional, cognitive, and behavioral dimensions of student engagement, considering factors such as gender, socio-economic status (SES), and cultural knowledge and experiences. A survey was conducted among students in a Chinese secondary school, with participants completing it using traditional pen and paper. Regression analysis was performed on the collected data to determine the influence of bicultural identities on student engagement, while considering the effects of gender, SES, and cultural knowledge and experiences. The findings indicate that students with resilient bicultural identities show significantly higher levels of emotional, cognitive, and behavioral engagement in school compared to those with weaker bicultural identities. This highlights the importance of nurturing and supporting students' ethnic, national, and cultural identities to enhance their overall engagement and participation in education. The results underscore the significance of recognizing and embracing students' dual cultural backgrounds, creating an inclusive environment, and employing culturally relevant educational approaches. This research has implications for educators, policymakers, and stakeholders in promoting a culturally inclusive educational system. It emphasizes the need to acknowledge and assess students' diverse cultural backgrounds and suggests the benefits of incorporating culturally responsive pedagogy and support systems to enhance student engagement and academics success. By understanding the impact of bicultural identities on student engagement, educators can establish an environment that fosters support and empowerment, contributing to students' overall educational experiences and outcomes.